MODEL PENGEMBANGAN STRATEGI PEMASARAN BERBASIS TEKNOLOGI INFORMASI DALAM MENINGKATKAN DAYA SAING UMKM DI JEPARA - Sisno Riyoko; Budi Lofian (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2020)
This study wanted to produce a model for developing marketing strategy based on Information Technology (IT) is a form of marketing strategy development model by taking into account and utilize Information Technology. The purpose of this study was to better efficiency at enhancing the competitiveness of SMEs through the use of Information Technology. Micro, Small and Medium cultivated IT base is expected will be increased competitiveness. Objective: 1) undescrebed  conditions of SMEs that have used information technology. 2) completion of a development model of IT-based marketing strategies that can be applied practically. 3) application  models empirically, and 4) unprovable  floating model application of IT-based marketing strategy. To achieve these objectives do action research approach, is research activities continued with implementation. Therefore, the model-based marketing strategy information technology into solutions for marketing problems of SMEs and increasing competitiveness.